The Psychology of Habit Theory, Mechanisms, Change, and Contexts (Springer International Publishing, 2018)
This unique reference explores the processes and nuances of human habits through social psychology and behavioral lenses. It provides a robust definition and theoretical framework for habit as well as up-to-date information on habit measurement, addressing such questions as which mechanisms are involved in habitual action and whether people can report accurately on their own habits. Specialized chapters pay close attention to how habits can be modified, as well as widely varying manifestations of habitual thoughts and behaviors, including the mechanisms of drug addiction and recovery, the repetitive characteristics of autism, and the unwitting habits of health professionals that may impede patient care. And across these pages, contributors show the potential for using the processes of maladaptive habits to replace them with positive and health-promoting ones. Throughout this volume attention is also paid to the practice of conducting habit research. Among the topics covered: Habit mechanisms and behavioral complexity. Complexities and controversies of physical activity habit. Habit discontinuities as vehicles for behavior change. Habits in depression: understanding and intervention. A critical review of habit theory of drug dependence. Questions about the automaticity of habitual behaviors. The Psychology of Habit will interest psychologists across a wide spectrum of domains: habit researchers in broader areas of social and health psychology, professionals working in (sub)clinical areas, interested scholars in marketing, consumer research, communication, and education, and public policymakers dealing with questions of behavioral change in the areas of health, sustainability, and/or education.